Comparative Water Quality Indexing of Three Different Water Bodies in Siwan City, Bihar: Comparative Analysis of Water Quality and WQI Models in Siwan City, Bihar (Journal of Advances and Scholarly Researches in Allied Education, 2021)
An effective way to gauge surface water quality is to use the Water Quality Index (WQI) model. It makes use of methods like as aggregation to reduce a large amount of water quality data to a single number. Using local water quality criteria, the WQI model has been used throughout the world to assess water quality (surface and groundwater). It's been a popular tool since the 1960s when it was first developed because of its basic structure and simplicity of use. This paper presents a comparative discussion of the most commonly used WQI models, including the different model structures. The focus of this study is on analysis of physiochemical parameters and WQI value of different type of lakes in siwan. The findings obtained from the quality analysis confirm that the water quality of Gargatwa canal Lake may not be acceptable for household uses. Disposing industrial wastewater into lake system has raised the possibilities of severe localized pollution and danger to the environment.